Pemanfaatan Fly Ash dan Bottom Ash Sebagai Adsroben dalam Menurunkan Parameter COD dan BOD pada Limbah Cair Tahu - Badu, Risti Ristianingsih; Kunusa, Wiwin Rewini; Umadji, Nur Inda R.; Paramata, Mulyani Zahra; A, Anisyah A. MS. (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The demand for clean water in Indonesia has been steadily increasing, but water pollution from industrial wastewater, especially from tofu production, remains a significant challenge. This study investigates the potential of fly ash and bottom ash as adsorbents to reduce chemical oxygen demand (COD) and biochemical oxygen demand (BOD) in tofu wastewater. Laboratory experiments were conducted with different adsorbent doses of 25, 50, and 75 grams. The adsorption process involved stirring the samples for 60 minutes, followed by a sedimentation period of 120 minutes. The results showed that fly ash was more effective than bottom ash in reducing COD and BOD levels. At a dose of 75 grams, Fly Ash achieved a 72% reduction in COD (from 0.8672 mg/L to 0.2438 mg/L) while Bottom Ash resulted in a 68% reduction with a final COD concentration of 0.2735 mg/L. A similar pattern was observed in the reduction of BOD. These results indicate that both fly ash and bottom ash can be effective and environmentally friendly alternatives for the treatment of tofu wastewater.